2022
DOI: 10.3390/jpm12101611
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Estimated Pulse Wave Velocity with Cardio-Vascular Disease Outcomes among Men and Women Aged 40–69 Years in the Korean Population: An 18-Year Follow-Up Report on the Ansung–Ansan Cohort in the Korean Genome Environment Study

Abstract: The estimated pulse wave velocity (ePWV) can predict adverse cardiovascular disease (CVD) outcomes in patients with increased CVD risks. However, data on its predictive capacity for CVD outcomes in the general population are limited. This study aimed to investigate the association between the ePWV and CVD outcomes among Korean adults. Ten thousand thirty patients aged 40–69 years from the Ansung–Ansan cohort in a prospective community-based cohort study were followed up for over 18 years. The ePWV was categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Prior studies have published findings regarding the prognostic value of ePWV. In the general population, an elevated baseline ePWV has been linked to an increased likelihood of subsequent cardiovascular events or mortality [ 18 , 19 , 20 ]. Additionally, the prognostic value of ePWV in patients at a moderate or high risk has been revealed by some research.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have published findings regarding the prognostic value of ePWV. In the general population, an elevated baseline ePWV has been linked to an increased likelihood of subsequent cardiovascular events or mortality [ 18 , 19 , 20 ]. Additionally, the prognostic value of ePWV in patients at a moderate or high risk has been revealed by some research.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, data were collected using an on-site interview questionnaire to ascertain the incidence of recent MI, CAD, stroke, HF, and PAD during biennial visits. MI was defined as a clinical emergency where the patient recalled experiencing a heart attack episode that necessitated hospitalization or revascularization [31]. CAD was defined as requiring hospitalization or revascularization, excluding any incidents of MI recalled by the patient.…”
Section: Study Outcomesmentioning
confidence: 99%
“…However, measuring cfPWV requires specialized equipment and trained staff, making it less accessible in clinical practice. In recent years, the Reference Values for Arterial Stiffness Collaboration has developed an equation called estimated pulse wave velocity (ePWV) that estimates aortic stiffness based on age and blood pressure (BP) (5).The ePWV has demonstrated comparable predictive efficiency to cfPWV in predicting major cardiovascular events (6,7) and Korean Population (8).Several studies have shown the associations of ePWV with cardiovascular outcomes, including stroke events, among Western populations (7,9). However, there is a lack of research on the relationship between ePWV and cardiovascular outcomes in Chinese populations.…”
Section: Introductionmentioning
confidence: 99%